Combating misinformation in the COVID-19 vaccine supply chain - DuBois, D.; Hoş, Rabia; Ashraf, Muhammad; Yalcin, Mehmet (Academy of Management Proceedings, 2025)
Keywords: Conceptual framework; Conceptual model; Misinformation; Stakeholder; Stakeholder engagement; Supply chain; Supply chain management; dept.grad

Bridging Borders: Teacher Perspectives on Refugee Students’ Schooling in Germany and the U.S. - Beck, Abby; Becker, Carmen; Hoş, Rabia (Multicultural Perspectives, 2025)
Keywords: Bridging (networking); Citizenship; Immigration; Qualitative research; Refugee; Teacher education; dept.grad

Syria, English in - Hadid, Alia; Hos, Rabia (The Wiley Blackwell Encyclopedia of World Englishes, 2025)
To gain a full perspective about English in Syria, it is necessary to focus on English learning in the past and present. The focus of the learning and teaching of the English language in Syria prior to 2011 consisted of various factors such as length of exposure to language, teacher preparation, qualifications, cross-linguistic transfer, and textbooks. The interruptions in schooling, brain drain, and depletion of resources were additional factors that influenced the learning and teaching of English in Syria in the post-2011 era. The entry concludes with a proposal that conscientious efforts are needed to enhance the teaching of English in Syria.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781119518297.eowe00398
Keywords: Computer science; English language teaching; English learning; Geography; History; Linguistics; Middle East; Philosophy; Syria; Syrian refugees; dept.grad; language education; teacher training

Empathy in action: nurturing sustainable educational change through Nel Noddings' ethics of care - Hadid, Alia; Hos, Rabia; Hauber-Özer, Melissa (Journal of Ethnic and Cultural Studies, 2025)
This introduction synthesizes the research presented by the contributors to this special issue to explore sustainable educational practices for refugees. A common thread across the articles is that they share components of Nel Noddings’ ethics of care framework, which emphasizes establishing welcoming, nurturing, and supportive environments that enable refugees to build meaningful relationships while honoring their cultural identities. We recommend action steps gleaned from the 11 papers in this issue that call for the concerted efforts of all those involved. Central to this vision are teachers, who serve as the backbone of the education system; however, to fulfill this role, they must be equipped with the necessary resources and skills to foster culturally responsive educational environments that emphasize students’ identities and provide equitable learning. This introduction underscores the importance of holistic and relational approaches as foundational to achieving sustainable educational equity for refugee learners.
Number: 2
Keywords: Community; dept.grad; empathy; empowerment; equity; inclusive; peer-reviewed